Competitive Diffusion of Trade Agreements in Latin America - Quiliconi, Cintia (2014)
Preferential Trade Agreements (PTAs) have rapidly proliferated in Latin America since the 2000s; this paper examines the factors which have facilitated or hampered their diffusion. The paper argues that the diffusion of PTAs, and resistance against them, has resulted in two alternative trade-integration models. On one hand, there is diffusion of US-led neoliberal North-South PTAs in Central American and Latin American countries (LACs) on the Pacific Basin. On the other hand, the reinforcement of post-liberal regionalism led by Brazil and MERCOSUR countries has acted as a firewall of resistance to the diffusion of US-led PTAs and their neoliberal policies. This paper first discusses how the competitive diffusion of US-led PTAs started in Latin America. It then analyzes two intertwined dynamics (international-regional and institutional-domestic) that explain why US-led PTAs have proliferated in the region. The third section explores MERCOSUR?s reactions to the US competitive PTA diffusion and also how Brazilian leadership has evolved in the South American subregion to encircle U.S. diffusion of PTAs, leading to an outcome of two different patterns of integration in Latin America.